Theoretical perspectives and conceptual approaches in biographical studies of culture and the arts (Mongolian Journal of Arts and Culture, 2025)
Biographical research is a viable and valuable approach across all scientific disciplines. Within the realm of Mongolian cultural and art studies, the examination of individuals who have played a historically significant role offers insight into the development of these fields during particular periods. Such an approach allows scholars to analyze underlying causes, contextual interrelations, and the influence of dominant ideologies, perspectives, and individual initiatives. In recent years, there has been an increasing societal demand for more comprehensive and multidimensional biographical studies. This paper seeks to provide an overview of the development of biographical research in the domains of culture and the arts. By exploring the theoretical underpinnings and conceptual orientations of biographical inquiry, the study aims to offer both scientific and practical contributions for future researchers. Accordingly, the paper outlines the trajectory and current state of biographical research within the scientific landscape of Mongolian society. In this study, the theoretical and methodological foundations of biographical research in the field of culture and the arts are examined. The biography of a historical individual is analyzed using a combination of hermeneutic methods, contextual historical documentation, content sampling, critical analysis, comparison, and synthesis. From this perspective, the study of biographies of prominent figures in the field of culture and the arts emphasizes the use of a new trend in biographical research known as personal history. This approach seeks to reconstruct the subject’s life as comprehensively and authentically as possible. While it may carry elements of individual subjectivity, it simultaneously encompasses the broader historical context of societal, cultural, artistic, and literary developments, thereby rendering it both innovative and significant in terms of academic and cultural value. It is also essential to examine the life and work of the individual in relation to the historical context in which they lived and created, taking into account the influence of both internal and external socio-cultural and environmental factors that shaped their personal and professional trajectory.Соёл, урлагийн намтар судлалын онол, үзэл баримтлалХураангуй: Намтар судлалыг аль ч шинжлэх ухааны салбарт судлан үзэх бүрэн боломжтой. Монголын соёл, урлаг судлалын салбарт түүхэн үүрэг гүйцэтгэсэн бие хүний намтрыг судалснаар тухайн үед тус салбар хэрхэн хөгжиж байсан талаар мөн түүний шалтгаан, хамаарал, ямар үзэл бодол, чиг хандлагатай хүмүүсийн санал, санаачилга хэрхэн нөлөөлсөн зэргийг тодруулах боломжтой. Сүүлийн жилүүдэд намтар судлалын судалгааг олон талаас судлан тодруулах нийгмийн шаардлага үүсэж байгаа тул соёл, урлагийн намтар судлалын хөгжлийг тоймлон үзүүлэхийг зорив. Соёл, урлагийн намтар судлалын онол, үзэл баримтлалыг авч үзсэнээр дараагийн судлаачдад шинжлэх ухааны хийгээд практик ач холбогдолтой юм. Иймийн тул монгол нийгмийн шинжлэх ухааны салбарт намтар судлалын судалгаа хэрхэн хөгжиж буйг тоймлон авч үзлээ. Энэхүү судалгаанд соёл урлагийн салбарын намтар судлалын асуудлын онол, үндэслэлийн асуудлыг авч үзэхдээ түүхэн бие хүний намтрыг герменевтик, түүхэн нөхцөл байдлын баримтын түүвэрлэлт, задлан шинжилгээ, харьцуулалт, нэгтгэн дүгнэх арга зүйг ашигласан болно. Энэ үүднээс соёл урлагийн салбарын нэрт хүмүүсийн намтрыг судлахдаа намтар судлалын шинэ чиг хандлага болох Personal history буюу “хувь хүний түүх”-ийг ашиглаж, аль болох бүрэн бүтнээр нь сэргээхийг чухалчлах, энэ нь хувийн бодигалаг шинжтэй хэдий боловч нөгөөтээгүүр нийгэм, соёл, урлаг, утга зохиолын хөгжлийн өргөн цар хүрээний түүхийг хамарсан онцлогтой болдгоороо шинэлэг, ач холбогдолтой болох юм. Түүнчлэн тухайн хүний амьдрал үйл ажиллагааг түүний аж төрж, бүтээн туурвисан түүхэн цаг үеийн нөхцөл байдал, нийгэм, соёлын гадаад дотоод орчны хүчин зүйлсийн нөлөөтэй уялдуулан авч үзэх нь чухал болно.Түлхүүр үгс: намтар судлал, хамрах хүрээ, онцлог, чиг хандлага, нөхцөл байдал